2010
DOI: 10.1111/j.1365-2559.2010.03574.x
|View full text |Cite
|
Sign up to set email alerts
|

Pleuropulmonary pathology of vascular Ehlers–Danlos syndrome: spontaneous laceration, haematoma and fibrous nodules

Abstract: Spontaneous laceration of lung tissue is an essential feature and is followed by haematoma and possible fibrous nodule formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 14 publications
2
32
0
Order By: Relevance
“…In previous reports, unilateral pneumothorax in EDS was not fatal (2). Hemorrhagic pulmonary complications are less described (5,13,14). The connective tissue of the vessel walls and internal organs, particularly that of the liver and lung, shows distinct hypoplasia, and type III collagen is significantly reduced (3).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In previous reports, unilateral pneumothorax in EDS was not fatal (2). Hemorrhagic pulmonary complications are less described (5,13,14). The connective tissue of the vessel walls and internal organs, particularly that of the liver and lung, shows distinct hypoplasia, and type III collagen is significantly reduced (3).…”
Section: Discussionmentioning
confidence: 98%
“…The connective tissue of the vessel walls and internal organs, particularly that of the liver and lung, shows distinct hypoplasia, and type III collagen is significantly reduced (3). This may cause increased fragility of the lungs and may present characteristic radiological findings, such as distributed cavities, fibrous nodules, and calcified lesions (5,15). Furthermore, pleural rupture may lead to pneumothorax or pneumohemothorax.…”
Section: Discussionmentioning
confidence: 99%
“…Type 3 collagen is a key element in the structure of arterial walls, viscous organs, and lung parenchyma. The pathogenesis of associated respiratory complications is unclear, though they are thought to result in fragility of the lung structures [8]. This deficit of type 3 collagen that constitutes the vascular walls and lung parenchyma may lead to pulmonary artery rupture or tears in the lung parenchyma, which may appear as characteristic changes of the lung in vEDS cases [4,5,9].…”
Section: Discussionmentioning
confidence: 99%
“…Kawabata et al . previously reported that most pulmonary lesions consist of idiopathic lung tissue lacerations [10]. Chest CT has been reported to show ground glass opacity due to bleeding, a tumor-like shadow due to the presence of a hematoma, a cavernous opacity following the formation of the hematoma, or a cystic shadow and a calcified opacity [6,8,11,12].…”
Section: Discussionmentioning
confidence: 99%